1998
DOI: 10.1590/s0037-86821998000200007
|View full text |Cite
|
Sign up to set email alerts
|

Revisión de los aspectos biológicos y diagnósticos del Trypanosoma (Herpetosoma) rangeli

Abstract: Resumen Esta revisión tiene tres objetivos básicos: a) estimular aún más la investigación de esta prevalente infección humana. b) examinar el arsenal de técnicas diagnósticas disponíbles al momento y, las nuevas pruebas descritas recientemente. c) enfatizar el significado que tiene, el parasitismo por el Trypanosoma (Herpetosoma) rangeli, en las áreas endémicas de la Enfermedad de Chagas distribuidas en las Américas Central y del Sur. Trypanosoma rangeli y Trypanosoma cruzi son parásitos que circulan superponi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
4

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(24 citation statements)
references
References 45 publications
(19 reference statements)
1
15
0
4
Order By: Relevance
“…rangeli is considered to be pathogenic to its invertebrate hosts, being responsible for triatomine death (1,6,41,42). It is known that several aspects of the physiology of the triatomines are altered during infection by T. rangeli, including reduced immune responses, anti-hemostatic activity of the salivary glands, and behavioral changes such as molting delays, changes in the movements of the insects, decreased reproductive performance and increased mortality (29,43,44).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…rangeli is considered to be pathogenic to its invertebrate hosts, being responsible for triatomine death (1,6,41,42). It is known that several aspects of the physiology of the triatomines are altered during infection by T. rangeli, including reduced immune responses, anti-hemostatic activity of the salivary glands, and behavioral changes such as molting delays, changes in the movements of the insects, decreased reproductive performance and increased mortality (29,43,44).…”
Section: Discussionmentioning
confidence: 99%
“…The most notable biological characteristic of T. rangeli in its invertebrate hosts is the passage of parasites from the intestine into the hemolymph and then to the insect salivary glands, where the protozoan develops infective metacyclic trypomastigotes. Then, they become infective to the vertebrate host through the bite of the insect vector (1)(2)(3). Rhodnius specimens are particularly susceptible to infection with T. rangeli; 13 of 19 Rhodnius species were reported to be infected with this parasite (4,5).…”
mentioning
confidence: 99%
“…Herpetosoma sub-genus species usually have specific hosts; however, T. rangeli presents a wide range of vertebrate reservoirs distributed among 5 orders: Edentata, Marsupialia, Carnivora, Rodentia and Primates (D'Alessandro 1976, D'Alessandro-Bacigalupo & GoreSaravia, 1992, Cuba Cuba 1998. Different species, including rats, mice, hamsters, rabbits, dogs, guinea-pigs, bat and primates have all been experimentally infected with T. rangeli.…”
Section: Reservoirsmentioning
confidence: 99%
“…It has been observed that the triatomids (particularly from the Rhodnius genus) are susceptible to T. rangeli strains having the same geographical origin (Cuba Cuba et al 1972, Cuba Cuba 1998, D'Alessandro 1976, D'Alessandro-Bacigalupo & Gore-Saravia 1992, Machado et al 2001). Several T. rangeli strains have shown variable behaviour in different Rhodnius species; for example, strains from Colombia and Costa Rica do not produce metacyclic tripomastigotes in R. pallescens or R. ecuadoriensis.…”
Section: Vector Susceptibility To Infection With T Rangelimentioning
confidence: 99%
“…The criteria of inclusion were also accessibility and entrance permission by the government and farmers. Classical parasitological 7 and molecular techniques (see below) were used for detecting natural infection by trypanosomatids.…”
Section: Study Areasmentioning
confidence: 99%